R2R / Nor Baitie Nor Abidin … [et al.] - Nor Abidin, Nor Baitie; Wan Mohd Zain, Wan Nurfatihah; Azmi, Shaheera; Ahmad Kilani, Nuraiman Athirah; Ahmad Zawawi, Ahmad Nasril Zaiyad (Research Innovation Business Unit, 2014)
The world has evolved into a globalization and modernized world, people are still enjoying the pleasure of relaxing while reading their favourite book, novel or magazine. We can’t deny that, printed media is still preferable and enjoyable to read. The problem now is that it is hard to read books at certain places as some place does not provide a convenient and comfortable stool. We have developed a product that can make book enthusiasts feel relaxed while reading their favourite book. The name of this product is r2r which means “relax to read”. This product consists of book rack, and mini comforter. This product allows readers to lean and even lie down while reading their favourite book. The materials for this product are plywood, hinge, plank, nail, screw, and sponge paper. Which is why, it is surprisingly light. The r2r is durable as it is very sturdy. The portability of this product which makes it more unique as it can be carried everywhere. The future of this product is bright and we focus on attracting avid readers. Apart from that, the r2r can be used for something else as the book compartment can be replaced by something else depends on the item which are to be put there. But, the weight must not be more than four kilos, as it will be difficult for the carrier to lift the r2r. The r2r also can be used during fishing trips. The book compartment can be installed with fishing rods gears and while fishing, fishers can relax while waiting for the fishes to eat their bait. The usage of r2r depends on the user needs and their creativity in using the r2r. Nonetheless, the r2r proves to be an efficient product to satisfy the needs of today’s societies. We believe that if a product proves to be useful for the society, the sales will be encouraging as the product is accepted by the market. The same concept goes to the r2r. The product is economical, portable, easy and light. It is pretty much what society needs in their daily lives for their activities.